Influence of Family Support and DM Status with Hemodialysis Patient’s Quality of Life - Anikha Widya Bestari (Jurnal Berkala Epidemiologi, 2016)
Management of CKD (Chronic Kidney Disease) in the final stage that is mostly done in Indonesia is hemodialysis. Psychosocial problems such as lack of family support sometimes become severe problems that must be faced by hemodialysis patients. Diabetes Mellitus (DM) as a cause of CKD is also a health problem that greatly increases the risk of morbidity and mortality for patients. This study aims to analyze the effect of family support and DM status on the quality of life of hemodialysis patients. This research was an observational analytic study with a cross-sectional design. The sample of this study were 72 patients at the Hemodialysis Installation of the Haji Public Hospital (RSU Haji) Surabaya, which was calculated using simple random sampling through a list of hemodialysis schedules. Data collection was carried out using interviews and looking at secondary data on patient examination documents. The questionnaire used was the WHOQOL-BREF questionnaire and the family support questionnaire. The results showed that there was an influence between family support (p = 0.005) and DM status (p = 0.003) on the quality of life status of patients. The conclusion of this study is the quality of life of hemodialysis CKD patients at Haji Hospital Surabaya is influenced by the family support they receive and DM status. DM status is the variable that most strongly influences the quality of life. Therefore, the intervention is focused on controlling patients with DM and supportive therapy in families.